(untitled) (Heteroglossia – studia kulturoznawczo-filologiczne, 2019)
Michał Witkowski’s novel Drwal (The woodcutter) shows various approaches to the subject of sexuality, what seems particularly inspiring, cognitively valuable and important from the perspective of this article is corporeality connected with elements related to money and finances, which are based on an integral, inseparable connection of two – seemingly not directly related – areas: sex and finances. For the novel’s protagonists, these two areas are inextricably complementing each other. The goal of this article is to examine and interpret the images of sexuality related to the sphere of finances presented by Witkowski, to understand their functions, to consider the consequences of combining these two areas, and to analyze the relationship between erotica relationship with the financial sphere and the uneroticizing of human sexuality. Thus the aim of this text is to verify whether the sexuality described in the novel is devoid of eroticism. Further, the paper discuse the manner of presenting these approaches to sexuality. The article also considerate the language of showing this specific approach to sexuality and reflection on its implications.